Designing data collection tools for psychiatric research: a practical guide for postgraduate psychiatry trainees - Darshankumar K. Dharaiya (International Journal Of Community Medicine And Public Health, 2026)
Data collection tools are used to document information gathered from participants or clinical records. Their structure and content vary depending on the study type, instruments used, and variables of interest. A poorly designed tool introduces systematic errors that no statistical method can correct. Since data collection is an irreversible step, and the quality of all downstream analyses depends on what is collected and how it is documented, careful attention to tool design is essential. This guide provides a structured, practically oriented framework for designing paper-based data collection tools in psychiatric research, covering study type, format, language, ordering, coding, and data entry compatibility.